Conductive polymers derived heteroatom doped carbon catalysts for oxygen reduction reaction - Honorato, Ana Maria Borges (2020)
Fuel cell is an electrochemical energy conversion system, that holds the promise for clean and sustainable energy source. During the operation, this device generates electricity direct from electrochemical reactions between electrodes and electrolyte. The limiting half-cell oxygen reduction reaction (ORR) that takes place at cathode is kinetically sluggish and needs catalysts to overcome the thermodynamic limitations by increasing the rate of catalytic ORR. So far, platinum Pt-based catalysts have been proven the best electrocatalyst, however, they suffer with high cost, poor stability, and limited reserves in the Earth’s crust, restricting their use for commercial purpose. In this context, the search for metal-free carbon nanomaterials have emerged as an alternative to the counterpart Pt-based catalysts, especially owing to excellent electrical conductivity, large surface area, good stability, and low cost. This dissertation compiles the research work on heteroatom doped (single and co-doped) carbon catalysts for ORR electrocatalysis in alkaline medium. For the preparation of doped carbon nanomaterials, the conductive polymers, for example polyaniline (PANI), poly (3,4-ethylenedioxythiophene) (PEDOT), and polythiophene (PTH) were chosen as the precursors and sequentially polymerized by oxidative polymerization method onto silicon dioxide (SiO2) and silicon nitride (Si3N4) nanospheres followed by carbonization process. The selection of conductive polymers to obtain doped carbon nanomaterials was based on the following reasons: low-cost monomers; presence of heteroatom in the monomer unit, and intrinsic conductivity. By selecting an appropriate synthetic route for the preparation of conductive polymers coated on the templates (SiO2 and Si3N4), we produced high surface area, abundant mesoporous, and intrinsically doped carbon nanomaterials with ORR activity in alkaline medium.